The Influence of Factors on the Demand for Performance Auditing in the Public Sector - Dang Anh Tuan; Nguyen Ngoc Khanh Dung (Ital Publication, 2024)
Performance audits (PA) are becoming essential in supreme audit institutions (SAIs). This study aims to explain why developing countries need to expand the function of PA and to explore and measure the impact of each factor on the need to develop PA in Vietnam. The research combines qualitative (group discussion) and quantitative methods by surveying 157 state auditors of the State Audit of Vietnam (SAV). Data is processed through SmartPLS 4.0.8.5 to verify the measurement and linear structure models. The results of the statistical analysis also show that all three factors have an impact on the development of PA, including (i) the degree of public governance reform, (ii) the accountability of SAV, and (iii) occupational influence. Besides, the model test results show that, from the perspective of SAV, the need to improve performance is higher than accountability. Public governance reform factors, external support, and SAI accountability contribute to enhancing the value of PA. The findings of this study complement the audit theory on three fronts: (i) PA will become more important when pursuing the goal of increasing accountability rather than improving performance; (ii) PA continues to evolve to adapt to social changes; and (iii) additional empirical evidence demonstrating that countries with low levels of transparency and accountability and inconsistent legal systems have higher audit “demand” but low supply of PA. This study proposes a PA development model to: (i) forecast the ability and level of the development audit of each SAI; and (ii) contribute to enhancing the value of PA using the PA topic selection tool. In addition, the developed scale is tested to ensure its reliability and validity. So this scale can be used to survey the needs, feasibility, and expected value that each audit subject brings before and after implementation. Doi: 10.28991/ESJ-2024-08-01-07 Full Text: PDF